Point of care Xpert MTB/RIF versus smear microscopy for tuberculosis diagnosis in southern African primary care clinics: a multicentre economic evaluation. Issue 6 (June 2019) - Pooran, Anil; Theron, Grant; Zijenah, Lynn; Chanda, Duncan; Clowes, Petra; Mwenge, Lawrence; Mutenherwa, Farirai; Lecesse, Paul; Metcalfe, John; Sohn, Hojoon; Hoelscher, Michael; Pym, Alex; et al.
Summary: Background: Rapid on-site diagnosis facilitates tuberculosis control. Performing Xpert MTB/RIF (Xpert) at point of care is feasible, even when performed by minimally trained health-care workers, and when compared with point-of-care smear microscopy, reduces time to diagnosis and pretreatment loss to follow-up. However, whether Xpert is cost-effective at point of care remains unclear. Methods: We empirically collected cost (US$, 2014) and clinical outcome data from participants presenting to primary health-care facilities in four African countries (South Africa, Zambia, Zimbabwe, and Tanzania) during the TB-NEAT trial. Costs were determined using an bottom-up ingredients approach. Effectiveness measures from the trial included number of cases diagnosed, initiated on treatment, and completing treatment. The primary outcome was the incremental cost-effectiveness of point-of-care Xpert relative to smear microscopy. The study was performed from the perspective of the health-care provider. Findings: Using data from 1502 patients, we calculated that the mean Xpert unit cost was lower when performed at a centralised laboratory (Lab Xpert) rather than at point of care ($23·00 [95% CI 22·12–23·88] vs $28·03 [26·19–29·87]). Per 1000 patients screened, and relative to smear microscopy, point-of-care Xpert cost an additional $35 529 (27 054–40 025) and was associated with an additional 24·3 treatment initiations ([–20·0 to 68·5]; $1464 per treatment), 63·4 same-day treatment initiations ([27·3–99·4]; $511 per same-day treatment), and 29·4 treatment completions ([–6·9 to 65·6]; $1211 per completion). Xpert costs were most sensitive to test volume, whereas incremental outcomes were most sensitive to the number of patients initiating and completing treatment. The probability of point-of-care Xpert being cost-effective was 90% at a willingness to pay of $3820 per treatment completion. Interpretation: In southern Africa, although point-of-care Xpert unit cost is higher than Lab Xpert, it is likely to offer good value for money relative to smear microscopy. With the current availability of point-of-care nucleic acid amplification platforms (eg, Xpert Edge), these data inform much needed investment and resource allocation strategies in tuberculosis endemic settings. Funding: European Union European and Developing Countries Clinical Trials Partnership and the South African Medical Research Council.